Computation of Topological Indices of Double and Strong Double Graphs of Circumcoronene Series of Benzenoid Hm - Muhammad Shoaib Sardar; Imran Siddique; Dalal Alrowaili; Muhammad Asad Ali; Shehnaz Akhtar (Journal of Mathematics)
Topological indices are very useful to assume certain physiochemical properties of the chemical compound. A molecular descriptor which changes the molecular structures into certain real numbers is said to be a topological index. In chemical graph theory, to create quantitative structure activity relationships in which properties of molecule may be linked with their chemical structures relies greatly on topological indices. The benzene molecule is a common chemical shape in chemistry, physics, and nanoscience. This molecule could be very beneficial to synthesize fragrant compounds. The circumcoronene collection of benzenoid Hm is one family that generates from benzene molecules. The purpose of this study is to calculate the topological indices of the double and strong double graphs of the circumcoronene series of benzenoids Hm. In addition, we also present a numerical and graphical comparison of topological indices of the double and strong double graphs of the circumcoronene series of benzenoid Hm.